The effect of cognitive sharing on strategic anxiety: Analytical research into the Iraqi Airways Company (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The current research aims to test the effect of knowledge sharing in its dimensions represented by(individual dimension, organizational dimension, and technological dimension), In reducing the strategic Anxiety of Iraqi Airways, In view of the importance of the two variables for the company from the perspective of society and the sample resulting from directing various organizational phenomena to reduce its strategic Anxiety, As a goal, it should be viewed from multifaceted perspectives(uncertainty, relational disorder, competitive disorder, resource depletion), And it was embodied by choosing the descriptive, exploratory approach, as it is the most appropriate in that aspect, so that the research questionnaire is one of solid scientific standards adopted by previous studies And some expert professors and arbitrators introduced appropriate modifications to it, as the research sample was intentional stratification from the company’s leadership community, which consisted of(general manager, department managers, divisional officials), It was used in some statistical programs(SPSS V.28) and through appropriate statistical methods(Descriptive statistical analysis through the mean, standard deviation, relative importance, coefficient of relative difference, multiple regression), The practical analysis, through the data obtained by the researcher from the sample answers, reached the most prominent result(Enables Iraqi Airways to embrace knowledge exchange To reduce its level of strategic Anxiety).